Highly Active Dinuclear Copper Catalysts for Homogeneous Azide-Alkyne Cycloadditions - Berg, Regina; Straub, Johannes; Damke, Ella; Mader, Steffen; Rominger, Frank; Straub, Bernd Franz (Advanced synthesis & catalysis, 2012)
The main feature of the herein presented class of molecularly defined catalysts for the copper-catalyzed azide-alkyne cycloaddition reaction is the presence of two copper centres in one catalyst molecule. We report the facile three-step synthesis of two representative bis-NHC-dicopper complexes as well as their catalytic performance in the azide-alkyne cycloaddition. A screening with one of these complexes has proved its wide applicability and excellent performance as homogeneous catalyst in various organic solvents and with different alkyne and azide substrates.
Gesehen am 23.04.2018